Given that p varies as the square of q and q varies inver...
Given that p varies as the square of q and q varies inversely as the square root of r. How does p vary with r?
p varies as the square of r
p varies as the square root of r
p varies inversely as the square of r
p varies inversely as r
Correct answer is D
p∝q2
q∝1√r
p=kq2
q=c√r
where c and k are constants.
q2=c2r
p=kc2r
If k and c are constants, then kc2 is also a constant, say z.
p=zr
p varies inversely as r.
In the diagram, PQR is a tangent to the circle QST at Q. If |QT| = |ST| and ∠SQR = 68°, find...
Solve: - 14 < 34 (3x - 2) < 12...
Differentiate (x2 - 1/x)2 with respect to x ...
If gt2 - k - w = 0, make g the subject of the formula...
Find the value of k if 5+2r(r+1)(r−2) expressed in partial fraction is \(\frac{k}...
The nth term of a sequence is n2 - 6n - 4. Find the sum of the 3rd and 4th terms....